LITERATURE STUDY: GROUND SURFACE SETTLEMENT DUE TO PIPE INSTALLATION WORKS USING THE PIPE JACKING METHOD - Easther Sistha Parameswari Wibisono; Aksan Kawanda (Universitas Trisakti, 2025)
Trenchless technology has been applied to minimize traffic, social, and commercial disruptions caused by construction works such as pipe installation. This technology includes pipe jacking, an underground boring method using hydraulic power. Soil disturbance due to pipe installation using the pipe jacking method is an element that must be considered and monitored during the construction and design process, because excessive ground surface settlement can potentially damage structures near the construction area. Over time, methods for predicting surface settlement continues to develop, including finite element and analytical method such as Peck’s, Verruijt’s, and Pinto’s formula. The variety of methods also encourages the growth of new characteristics and features in ground surface settlement due to pipe jacking, including the non-symmetrical ground surface settlement to the pipe axis in curved pipe jacking, the significant impact of jacking force magnitude and shield machine movement, to grouting as the impact mitigation of construction work damages.